Kinetic behaviour of Staphylococcus aureus on cheese as a function of water activity and temperature. Issue 1 (February 2015) - Lee, Heeyoung; Kim, Kyungmi; Lee, Soomin; Yoon, Yohan
<x content-type="archive" xml:space="preserve">Abstract</x> This study developed mathematical models in order to evaluate the effect of Aw (Water activity) and growth temperature on Staphylococcus aureus kinetic behaviour. The Aw levels (0·970, 0·975, 0·983, and 0·991) of cheese were adjusted by NaCl; then, Staph. aureus was inoculated on the cheese, followed by storage at 7–30 °C for 72–720 h. Total bacterial and Staph. aureus cell counts were enumerated on tryptic soy agar and mannitol salt agar, respectively. The Baranyi model was fitted to the Staph. aureus growth data in order to calculate the maximum specific growth rate (μmax; log CFU/g/h), lag phase duration (λ; h), lower asymptote (N0; log CFU/g) and upper asymptote (Nmax; log CFU/g). The effects of storage temperature and Aw on the kinetic parameters (μmax and λ) were then further analysed with the Ratkowsky-type model and a polynomial equation, respectively. The root mean square error (RMSE) and relative error (RE) were calculated in order to estimate the model performance. No significant effect of Aw on Staph. aureus growth was observed at 7 °C; thus, the Baranyi model was fitted to the growth data from 15, 25 and 30 °C. The μmax values (0·011–0·303 log CFU/g/h) increased (P<0·05) as the storage temperature and Aw increased. In addition, λ values (2·42–63·48 h) decreased (P<0·05) as storage temperature and Aw increased; yet, the effect of Aw on λ was observed only at 15 °C. The theoretical minimum storage temperature and Aw were 10·15 °C and 0·882, respectively. RMSE (0·010–1·544) and RE values (−0·131 to 0·187) from validation indicated that model performance was appropriate. Hence, these results suggest that the developed models in this study should be useful in describing the effect of temperature and Aw on the growth kinetic behaviour of Staph. aureus in cheese along with the exposure assessment of Staph. aureus in cheese as well.